Nitrogen supply in rice-based cropping systems as affected by crop residue management - Thuy, Nguyen Hong; Shan, Yuhua; Bijay-Singh; Wang, Kairong; Cai, Zucong; Yadvinder-Singh; Buresh, Roland J. (Wiley, 2008)
Concerns regarding the detrimental effects of burning crop residues on human health and the environment have increased interest in alternative uses of crop residues. We examined the in situ use of crop residue as a source of supplemental N for succeeding crops in rice (Oryza sativa L.)‐based cropping systems at three sites during 3 yr. The experiments included a rice–wheat (Triticum aestivum L.) rotation at Yixing, Jiangsu Province, China; a rice–wheat rotation at Ludhiana, Punjab, India; and double‐rice cropping at Taojiang, Hunan Province, China. The supply of N from crop residues was assessed in the absence of fertilizer N as the difference in total plant N between plots with and without residue. At Yixing, incorporation of wheat residue before rice significantly increased the N supply to the rice by 14 kg N ha−1 averaged across 3 yr. At Ludhiana, incorporation of rice residue before wheat reduced the N supply by 3 kg N ha−1 to the wheat, but increased the N supply by 5 kg N ha−1 to the rice crop following the wheat. In all cases, the return of crop residues had no net benefit on crop yield when fertilizer N was supplied at rates sufficient to eliminate N deficiency. The incorporation of crop residues did not increase the N supply to the succeeding crop during its vegetative growth phase, but the N supply to the crop at later growth stages was often increased. Adjustments in the timing and rate of fertilizer N are probably necessary to optimally supply N to crops receiving residues.